Service ecosystem well-being: conceptualization and implications for theory and practice. (13th September 2019) - Frow, Pennie; McColl-Kennedy, Janet R.; Payne, Adrian; Govind, Rahul
Abstract : Purpose: This paper aims to conceptualize and characterize service ecosystems, addressing calls for research on this important and under-researched topic. Design/methodology/approach: The authors draw on four meta-theoretical foundations of S-D logic – resource integration, resource density, practices and institutions – providing a new integrated conceptual framework of ecosystem well-being. They then apply this conceptualization in the context of a complex healthcare setting, exploring the characteristics of ecosystem well-being at the meso level. Findings: This study provides an integrated conceptual framework to explicate the nature and structure of well-being in a complex service ecosystem; identifies six key characteristics of ecosystem well-being; illustrates service ecosystem well-being in a specific healthcare context, zooming in on the meso level of the ecosystem and noting the importance of embedding a shared worldview; provides practical guidance for managers and policy makers about how to manage complex service ecosystems in their quest for improving service outcomes; and offers an insightful research agenda. Research limitations/implications: This research focuses on service ecosystems with an illustration in one healthcare context, suggesting additional studies that explore other industry contexts. Practical implications: Practically, the study indicates the imperative for managing across mutually adapting levels of the ecosystem, identifying specific new practices that can improve service outcomes. Social implications: Examining well-being in the context of a complex service ecosystem is critical for policymakers charged with difficult decisions about balancing the demands of different levels and actors in a systemic world. Originality/value: The study is the first to conceptualize and characterize well-being in a service ecosystem, providing unique insights and identifying six specific characteristics of well-being.